Characterization of Phenolic Constituents from Prunus cerasifera Ldb Leaves - Wei Liu; Muhammad Farrukh Nisar; Chunpeng Wan (Journal of Chemistry)
To elucidate the chemical compositions of Prunus cerasifera Ldb leaves, the methanol extracts were firstly fractionated by ethyl acetate and n-butanol, respectively. The phenolic acid-rich fractions (ethyl acetate extracts) were further isolated by various chromatographic columns (CC) including MCI macroporous resin, normal-phase silica gel, Sephadex gel LH-20, octadecyl silane (ODS), and preparative HPLC to yield the phenolic compounds. The isolated compounds were analyzed by 1H-nuclear magnetic resonance (1H-NMR), 13C-NMR, and electrospray ionization mass spectral (ESI-MS) spectroscopy. Eleven phenolic acids were identified as p-coumaric acid (1), caffeic acid (2), ferulic acid (3), chlorogenic acid (4), 3-O-caffeoylquinic acid (5), 5-O-coumaroylquinic acid (6), 3-O-caffeoylquinic acid methyl ester (7), chlorogenic acid methyl ester (8), 3-O-caffeoyl-5-O-coumaroylquinic acid or 3-O-coumaroyl-5-O-caffeoylquinic acid (9), gallic acid (10), and protocatechuic acid (11). The current study pioneers to identify and report all the phenolic constituents from P. cerasifera Ldb leaves.